Granulosain I, a cysteine protease isolated from ripe fruits of Solanum granuloso-leprosum (Solanaceae) - Vallés, Diego (2008)
A new cysteine peptidase (Granulosain I) was isolated from ripe fruits of Solanum granuloso-leprosum Dunal (Solanaceae) by means of precipitation with organic solvent and cation exchange chromatography. The enzyme showed a single band by SDS-PAGE, its molecular mass was 24,746 Da (MALDI-TOF/MS) and its isoelectric point was higher than 9.3. It showed maximum activity (more than 90%) in the pH range 7-8.6. Granulosain I was completely inhibited by E-64 and activated by the addition of cysteine or 2-mercaptoethanol, confirming its cysteinic nature. The kinetic studies carried out with PFLNA as substrate, showed an affinity (Km 0.6 mM) slightly lower than those of other known plant cysteine proteases (papain and bromelain). The N-terminal sequence of granulosain I (DRLPASVDWRGKGVLVLVKNQGQC) exhibited a close homology with other cysteine proteases belonging to the C1A family.